COVID-19 and SMEs: A 2021 "time bomb"? - Pierre-Olivier Gourinchas; Sebnem Kalemli-Ozcan; Veronika Penciakova; Nick Sander (Federal Reserve Bank of Atlanta, 2021)
This paper assesses the prospects of a 2021 time bomb in small and medium-sized enterprises (SME) failures triggered by the generous support policies enacted during the 2020 COVID-19 crisis. Policies implemented in 2020, on their own, do not create a 2021 time bomb for SMEs. Rather, business failures and policy costs remain modest. By contrast, credit contraction poses significant risk. Such a contraction would disproportionately affect firms that could have survived COVID-19 in 2020 without any fiscal support. Even in that scenario, most business failures would not arise from excessively generous 2020 policies but rather from the contraction of credit to the corporate sector.
Keywords: L26; E32; M21; 330; business formation; entrepreneurship; business dynamism; recessions